ANALISIS PENGELOLAAN KAWASAN HUTAN DI KHDTK UNIVERSITAS TANJUNGPURA - Gusti Hardiansyah; Dwi Yoga Budi Pranoto; Zuhry Haryono; A F Tanjung; Erianto Erianto; Iskandar A M; Sofyan Zainal; Iswan Dewantara (Tengkawang : Jurnal Ilmu Kehutanan, 2023)
KHDTK at Tanjungpura University is a forest area managed for education, research, and community service. This research objective is to analyze the management of KHDTK. Using field observation methods and interviews with KHDTK managers. The interview technique is carried out through in-depth interviews. Using two levels of analysis (1) qualitative descriptive analysis of management (2) content analysis of statutory regulations related to KHDTK. The results of the analysis explain environmental management through community involvement in the form of MPTS enrichment agroforestry, meeting household needs in the form of utilizing water sources and firewood. Forest management is carried out by planting RHL which expands its use for voluntary carbon and protecting/securing forests from forest and land fires, encroachment/illegal logging. Utilization of forest products in the form of NTFPs such as rattan, bajakah roots, resin, and honey. Funding resource management comes from DIPA funds from the Faculty of Forestry which are divided into research, PKM, KHDTK natural laboratory management, and Cooperation grant funds. The challenge in KHDTK management is the dominance of regulations governing KHDTK administration requirements such as PBPH which is profit-oriented, while KHDTK has special characteristics (cost center). The 10% area utilization limitation for funding investment opportunities seems to be lopsided with the specific aim of training and training which manages the landscape of forest areas requiring capital-intensive investment so that program management runs optimally.Keywords: analysis, KHDTK, Forest area management.AbstrakKHDTK di Universitas Tanjungpura (UNTAN) merupakan kawasan hutan yang dikelola untuk kepentingan pendidikan, penelitian, dan pengabdian kepada masyarakat. Tujuan dari penelitian ini untuk menganalisis pengelolaan KHDTK. Menggunakan metode observasi lapangan dan wawancara terhadap pengelola KHDTK. Teknik wawancara yang dilakukan melalui indept interview. Menggunakan dua tingkat analisis yaitu (1) analisis deskriptif kualitatif terhadap pengelolaan, dan (2) Analisis isi (content analysis) peraturan perundangan terkait dengan KHDTK. Hasil analisis menjelaskan pengelolaan lingkungan melalui pelibatan masyarakat dalam bentuk agroforestri pengayaan MPTS, pemenuhan kebutuhan rumah tangga berupa pemanfaatan sumber air dan pemanfaatan kayu bakar. Pengelolaan hutan yang dilakukan berupa penanaman RHL yang diperluas pemanfaatannya untuk voluntary karbon dan perlindungan/pengamanan hutan dari karhutla, perambahan/pembalakan liar. Pemanfaatan hasil hutan berupa HHBK seperti rotan, akar bajakah, getah damar, dan madu. Pengelolaan sumberdaya pendanaan bersumber dari dana DIPA Fakultas Kehutanan yang terbagi untuk penelitian, PKM, pengelolaan laboratorium alam KHDTK dan dana hibah Kerjasama. Tantangan pada pengelolaan KHDTK adalah dominannya peraturan yang mengatur persyaratan administrasi KHDTK seperti PBPH yang berorientasi profit, sedangkan KHDTK memiliki karakteristik khusus (cost center). Pembatasan pemanfaatan kawasan 10% untuk peluang investasi pendanaan seakan menjadi timpang dengan tujuan khusus diklat yang mengelola bentang alam kawasan hutan membutuhkan investasi padat modal agar pengelolaan program berjalan optimal. Kata kunci: analisis, KHDTK, Pengelolaan kawasan hutan.